PROFITABILITAS, LIKUIDITAS DAN NILAI PERUSAHAAN : STRUKTUR MODAL SEBAGAI VARIABEL INTERVENING DAN UKURAN PERUSAHAAN SEBAGAI VARIABEL KONTROL - Leni Fitria; Enis Khaerunnisa; Bambang Mahmudi (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2022)
This study was conducted to determine the effect of Profitability proxied by ROE (Return On Equity) and Liquidity proxied by CR (Current Ratio) on Company Value proxied by PBV (Price Book Value) through Capital Structure proxied by DER (Debt to Equity Ratio) as an intervening variable and firm size as a proxy with LN (Total Assets) as a control variable. The population used in this study are all Metal & Similar Sub-Sector Manufacturing Companies listed on the Indonesia Stock Exchange 2011-2019. The data analysis techniques in this study are statistical analysis, classical assumption test, multiple linear regression, hypothesis testing, path analysis test, and Sobel test using the SPSS program. The results of this study indicate that: (1) Profitability has a positive effect on firm value. (2) Liquidity has a negative effect on firm value. (3) Profitability has a positive but not significant effect on capital structure. (4) Liquidity has a negative effect on the capital structure. (5) Capital structure has a negative effect on firm value. (6) Capital structure is not able to mediate the relationship between profitability and firm value. (7) Capital structure is not able to mediate the relationship between liquidity and firm value. (8) Firm size as a control variable needs to be excluded because it has a positive and insignificant effect on firm value, so it cannot be used as a control variable.